The knowledge-risk-behaviour continuum among young Ugandans: what it tells us about SRH/HIV integration - Raquel Palomino González; Damazo Twebaze Kadengye; Roy William Mayega (BMC, 2019)
Abstract Background With a human immunodeficiency virus (HIV) prevalence of 2.1% among 15-24 year olds, opportunities for further integration of sexual and reproductive health (SRH) and HIV prevention services for young people in Uganda exist. We examine a range of factors that contribute to variance in risky sexual behaviour among young Ugandans. Methods A cross-sectional, nationally representative household survey was conducted between February and March 2016. The questionnaire used assessed knowledge, attitudes and practices related to SRH among young people aged 10-24 years. A composite indicator was constructed to assess risky sexual behaviour, defined as being involved in sexual relations under the influence of alcohol or drugs, engaging in sexual activities without a condom, and having multiple sexual partners in the 6 months preceding the survey. Exploratory analysis was conducted to provide descriptive statistics. Logistic regression was conducted to determine the factors associated with risky sexual behaviour. This analysis focuses on the sub-category aged 15-24 years, comprised of 2725 respondents. Results Knowledge levels of family planning (FP), sexually transmitted infections (STIs) and HIV across all respondents were high (above 82%). Self-reported perceived risk of STIs and pregnancy was consistently higher among 20-24 year old respondents, with 61.5% feeling at risk of STIs compared to 46.2% of 15-19 year olds. A total of 22.7% of respondents reported having been involved in risky sexual behaviour. Factors associated with risky sexual behaviour among the 15-19 years group included gender, single orphanhood, casual work, schooling status, FP knowledge and self-perceived risk of STIs/HIV. For the 20-24 year old respondents, significantly associated factors included gender, educational level, relationship to head of household, place of residence, and self-perceived risk of pregnancy. Conclusions Despite high general SRH/HIV knowledge and perceived risk of pregnancy and HIV, risky sexual behaviour among young Ugandans remains high. Effectiveness gaps in the integrated SRH/HIV response for young people should be addressed and targeted interventions focused on holistic prevention at individual level through information, risk awareness, and skill development should be combined with interventions targeting social structures affecting individual behaviour.